Double-layer Composite Film of Natural Materials and Mulch Film Application - Pinpru, Nattapong; Charoonsuk, Thitirat; Phanasun, Thanong; Soponpong, Machima; Bongkarn, Theerachai; Woramongkolchai, Somsak; Vittayakorn, Naratip (My University, 2022)
In this work, double-layer mulch composite film was prepared from natural materials (bacterial cellulose; BC, alginates, carboxymethyl cellulose; CMC, and calcium hydrogen phosphate; CaHPO4) by the solvent casting method. The BC/CaHPO4 film was casted as a second layer and serves two purposes: soil water absorption and slow-release fertilizer. The mechanical properties of the double layer film are significantly improved by using the double-layer casting technique with the tensile strength of 17.4 MPa and the percentage of elongation at break of 78.7%. The percentage of water absorption and biodegradation was increased to 60% and 48.7%, respectively, within 30 days. Morphological evidence confirmed that the double-layer composite film degraded gradually, as cracks appeared on its surface when buried in soil for a longer period of time. This result was consistent with increasing biodegradation percentage. In addition, the double-layer composite film fully supported the decrease in temperature and increase of soil moisture via ultra violet (UV) protection.
Keywords: alginates; bacterial cellulose; calcium hydrogen phosphate; carboxymethyl cellulose; doublelayer composite film